Initial Stroke Severity Is the Major Outcome Predictor for Patients Who Do Not Receive Intravenous Thrombolysis due to Mild or Rapidly Improving Symptoms. (27th July 2011) - Sun, Mu-Chien; Lai, Tien-Bao
Abstract : Intravenous tissue plasminogen activator thrombolysis for stroke is still under use. A substantial proportion of excluded patients for mild or improving symptoms are dependent at discharge. We prospectively recruited 49 patients who did not receive thrombolysis because of mild or improving symptoms. 32 had favorable outcome (mRS ≤ 2) and 17 had unfavorable outcome (mRS > 2) at discharge. Comparisons were made between the two groups. Age was older (72.5 ± 10.0 versus 64.7 ± 13.2 years, P = 0.037), and initial National Institutes of Health Stroke Scale (NIHSS) score (5.7 ± 4.0 versus 2.2 ± 2.1, P < 0.001) was higher in the unfavorable group. Diastolic blood pressure was higher in the favorable group (98 ± 15 versus 86 ± 18 mmHg; P = 0.018). Atrial fibrillation (3.1 versus 23.5%; P = 0.043) and ipsilateral artery stenosis (21.9 versus 58.8%; P = 0.012) were more frequently found in the unfavorable group. Percentage of patients excluded from thrombolysis due to improving symptoms was higher in the unfavorable group (40.6 versus 82.4%; P = 0.005). Initial NIHSS score, but not other factors, was identified by logistic regression analysis as a major independent predictor for unfavorable outcome (OR 1.44; 95%CI, 1.03–2.02).